Consumerism, sustainability, and happiness : how to build a world where everyone has enough - Kaufman, Cynthia C., 1960- (New York, NY : Routledge, 2023)
"What would it take to have a world where everyone had enough? How can we eliminate poverty, leave enough for non-human nature, and increase wellbeing? This book explores ways the reader can live their life, engage with cultural change, and engage with policy making, to build that world. We are presently on a path to environmental destruction, as our societies are driven by forces which leave many people without what they need to meet their basic needs, while also wasting vast resources on an unsatisfying consumer economy. The current system does not lead to a sense of wellbeing, even among those who are relatively materially comfortable. This book focuses on solutions for building a world of enough. It explains how we can reorient our thinking and take the steps necessary to transform our social systems. It looks at ways to reduce the insatiable desire for status and consumption that drive our economies. It focuses on emerging approaches to economics that take wellbeing as their goal, and explores the policies that are crucial for getting there, such as reducing inequality, investing in public goods, and reducing work time. The book arms the reader with a variety of tools for building a world where everyone has enough for a good life"--
Happiness, Poverty, Sustainability -- The Psychology of Enough -- Building a Life with Enough -- Economics Based on Scarcity and Infinite Growth -- Capitalism, Socialism, and Solidarity Economics -- Eliminating Extreme Poverty and Developing an Economics for Enough -- Policies and Politics to Get to a World of Enough.
Keywords: Social change; Consumption (Economics); Sustainability; Happiness; Human ecology; SOCIAL SCIENCE / Poverty; POLITICAL SCIENCE / Public Policy / Environmental Policy